The Struggle Out of Isolation Girl As Seen in Delia Owens’ Where The Crawdads Sing - Raflis Raflis; Asysyifa Hayatul Husna (Jurnal Ilmiah Langue and Parole, 2025)
This study explores the psychological impact of isolation and alienation as experienced by the protagonist, Kya Clark, in Delia Owens’ Where the Crawdads Sing. Using a qualitative descriptive approach, this research applies Erik Erikson’s theory of psychosocial development and the literary concepts outlined in Akhmedov’s Introduction to Literary Theory (2020). The analysis reveals how Kya’s prolonged isolation profoundly influences her identity formation, emotional resilience, and ability to establish trust and intimacy. By examining Kya’s journey through Erikson’s psychosocial stages—especially Trust vs. Mistrust, Identity vs. Role Confusion, and Intimacy vs. Isolation—this study identifies the psychological struggles and eventual growth of a girl forced into solitude by abandonment and social prejudice. The findings show that isolation, while a source of deep psychological trauma, also becomes a catalyst for Kya’s self-reliance, creativity, and emotional maturity. Nature functions as her symbolic mother and therapeutic space, providing the security and acceptance denied by human society. Owens’ novel illustrates how alienation can produce both emotional fragility and inner strength, showing the resilience of the human spirit amid social rejection and personal loss.